ANALISIS RESEPSI KHALAYAK TERHADAP PEMBERITAAN MAKAN SIANG GRATIS DI MEDIA MASSA - Azizi, Adira Dzaki; Vera, Nawiroh (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
The mass media coverage during the recent presidential campaign highlighted one of the programs proposed by the Prabowo-Gibran pair, namely the